EGLN2 DNA methylation and expression interact with HIF1A to affect survival of early-stage NSCLC. Issue 2 (1st February 2019) - Zhang, Ruyang; Lai, Linjing; He, Jieyu; Chen, Chao; You, Dongfang; Duan, Weiwei; Dong, Xuesi; Zhu, Ying; Lin, Lijuan; Shen, Sipeng; Guo, Yichen; Su, Li; et al.
ABSTRACT: Hypoxia occurs frequently in human cancers and promotes stabilization and activation of hypoxia inducible factor (HIF). HIF-1α is specific for the hypoxia response, and its degradation mediated by three enzymes EGLN1, EGLN2 and EGLN3 . Although EGLNs expression has been found to be related to prognosis of many cancers, few studies examined DNA methylation in EGLNs and its relationship to prognosis of early-stage non-small cell lung cancer (NSCLC). We analyzed EGLNs DNA methylation data from tumor tissue samples of 1, 230 early-stage NSCLC patients, as well as gene expression data from The Cancer Genome Atlas. The sliding windows sequential forward feature selection method and weighted random forest were used to screen out the candidate CpG probes in lung adenocarcinomas (LUAD) and lung squamous cell carcinomas patients, respectively, in both discovery and validation phases. Then Cox regression was performed to evaluate the association between DNA methylation and overall survival. Among the 34 CpG probes in EGLNs, DNA methylation at cg25923056 EGLN2 was identified to be significantly associated with LUAD survival ( HR = 1.02, 95% CI: 1.01–1.03, P = 9.90 × 10 –5 ), and correlated with EGLN2 expression ( r = – 0.36, P = 1.52 × 10 –11 ). Meanwhile, EGLN2 expression was negatively correlated with HIF1A expression in tumor tissues ( r = – 0.30, P = 4.78 × 10 –8 ) and significantly ( P = 0.037) interacted with HIF1A expression on overall survival. Therefore, DNA methylation of EGLN2- HIF1A is a potential marker for LUAD prognosis and these genes are potential treatment targets for further development of HIF-1α inhibitors in lung cancer therapy.